CORRÊA, Sergio; ANDREAZZA, Tiaraju; MACIEL, Everton (org.). Política Prática. Macapá: Universidade Federal do Amapá, 2020 - Delupi, Baal (Letrônica, 2020)
Corrêa, Sergio; Andreazza, Tiaraju; Maciel, Everton (org.). Política Prática. Macapá: Universidade Federal do Amapá, 2020